ERGO-MECHANICAL APPROACH OF DESIGNING TRUCK TIRE INSTALLATION TOOL FOR SMALL WORKSHOPS - Gede Bawa Susana; I Gusti Agung Ketut Chatur Adhi Wirya Aryadi; Hafiz Jefry (Jurnal Dinamika Vokasional Teknik Mesin, 2026)
Manual truck tire installation can cause musculoskeletal disorders due to unnatural postures and high physical demands. This study aims to assess the prevalence of musculoskeletal complaints among truck tire installation workers and to design a truck tire installation aid based on an ergo-mechanical approach. The level of musculoskeletal complaints was measured using the Nordic Body Map questionnaire with a four-point Likert scale in five workers, before and after work. The measurement results showed an average musculoskeletal complaint score of 54.2 after work, placing it in the moderate-risk category and requiring corrective action. Based on these findings, a truck tire installation aid was designed using worker anthropometric data, employing a 5th-percentile approach to ensure the safety and comfort of workers with small body sizes. The body dimensions used include standing elbow height, palm length, knee height, foot length, and horizontal standing reach. The results of translating anthropometric data into technical designs indicate that the proposed assistive device has the potential to improve work posture, reduce physical load, and lower the risk of musculoskeletal disorders. Although this research remains limited to the conceptual design stage and lacks prototype testing, the results can serve as a basis for developing and evaluating ergonomic assistive devices in real work environments.